21-gene recurrence score testing in the older population with estrogen receptor-positive breast cancer. Issue 2 (March 2019) - Kizy, Scott; Altman, Ariella M.; Marmor, Schelomo; Denbo, Jason W.; Jensen, Eric H.; Tuttle, Todd M.; Hui, Jane Yuet Ching
Abstract: Introduction: The 21-gene recurrence score (RS) (Oncotype Dx, Genomic Health, Redwood City Ca) has not been validated in an older cohort with estrogen receptor (ER)-positive breast cancer. The objective of this study was to evaluate RS validity in a group of older women with ER-positive breast cancer. Methods: Utilizing the Surveillance, Epidemiology, and End Results Program (SEER) database with available RS, we evaluated women with ER-positive breast cancer aged 18–69 and those 70 years of age and older from 2004 to 2014. We utilized multivariable logistic regression models to evaluate factors associated with RS testing as well as a high-risk categorization for those who underwent testing. Survival was analyzed using Kaplan Meier curves and Cox proportional hazard models. Results: We identified 363, 876 women aged 18–69 years and 147, 107 women aged 70 years and older. A smaller proportion of patients in the older group (8%) underwent RS testing than in the younger group (18%). Of the patients who underwent testing, distribution of RS was similar between groups. High-risk categorization independently predicted a higher likelihood of death for older patients (hazard ratio 1.47, 95% confidence interval 1.15–1.90). Among patients with high-risk RS, chemotherapy was associated with a decreased risk of death in the younger group, but not in the older group. Conclusion: Older women are less likely to receive RS testing, but when tested, older patients have a similar distribution of RS as compared to younger patients. While high-risk categorization in the older cohort was prognostic, chemotherapy was not associated with improved survival.